2007
DOI: 10.1111/j.1365-2222.2007.02687.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of allergenicity and immunogenicity of an intact allergen vaccine and commercially available allergoid products for birch pollen immunotherapy

Abstract: While some allergoids were associated with reduced allergenicity, a clear reduction in immunogenicity was observed for all allergoid products compared with the intact allergen vaccine, and the commercial allergoids tested therefore do not fulfil the allergoid concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…As expected, lysine residues were not detected by mass spectrometry in the digested Dpg-Pol extract because they are modified to establish covalent bridges between allergens. Several in vitro studies have suggested partial loss of T cell epitopes for various allergoid preparations [7,19,20]. If major allergens were lost or under-represented in allergoid immunotherapy preparations, this could potentially reduce their clinical and immunological efficacy in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, lysine residues were not detected by mass spectrometry in the digested Dpg-Pol extract because they are modified to establish covalent bridges between allergens. Several in vitro studies have suggested partial loss of T cell epitopes for various allergoid preparations [7,19,20]. If major allergens were lost or under-represented in allergoid immunotherapy preparations, this could potentially reduce their clinical and immunological efficacy in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced allergenicity (the key rationale behind the allergoid concept) is not always fulfilled. In fact, Lund et al [24] compared 4 different allergoid preparations with a native allergen, revealing that 1 even displayed greater allergenicity than the unmodified allergen. The potential to induce immediate allergic responses therefore needs to be tested for each allergoid on an individual basis to prove reduced allergenicity in comparison to the native extract.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profiles observed for allergoids may be related to the increased vaccine concentrations and quick updosing schedules used for allergoids. On the other hand, they may also be explained by the high degree of patient to patient variation observed for allergoids in basophil activation tests [13] and the variable allergenicity that we described previously for different nonstandardized commercially available allergoid products [24]. In addition to this, the IgE inhibition curves investigated previously indicated that the epitope composition of the birch allergoid differs from that of the birch extract, which underscores that the clinical effects of allergoids and allergen extracts each have to be documented in specific studies [24].…”
Section: Discussionmentioning
confidence: 99%